Pemikiran Tokoh Pendidikan Islam - Rosita Siregar; Zainal Efendi Hasibuan (STIKes Ibnu Sina Ajibarang, 2024)
Educations is guidance, leadrship,from educators to students with phsyical and spritual development, educations shapes the character, nature, and, behavior of student systematically. Educations is a development of students to develop the potential, reason. And abilities possessed by students. In educations have several figures in the science of educations. Understanding education is a conscious and planned effort to create an atmosphere learning procces for students to actively develop their potential to have spritual strength, self control, personality, intelligence, noble character, and the skills needed by themselves and the community. Undestanding education can be interpreted as as conscious and systematic efferots to achieve a standard of living or for better progrees, simply put, understanding educations is a learning procces for students to be able to understand, and make humans more critical in thingking.